The Middle Management Perspective on Strategy Process: Contributions, Synthesis, and Future Research - Wooldridge, Bill; Schmid, Torsten; Floyd, Steven W. (Journal of Management, 2008)
During the past 25 years, a substantial amount of research in strategic management has focused on the contributions of middle management. Although useful, the research is characterized by considerable diversity in terms of focal constructs and relationships. The purpose of this review is to organize this research and identify important constructs, relationships, and contributions. The review serves not only to catalog the state of the art and accumulate knowledge; it also facilitates the critique necessary for charting directions and enhancing the cumulative nature of future research.